Affordability of comprehensive community health worker programmes in rural sub-Saharan Africa. Issue 3 (25th September 2017) - Taylor, Celia; Griffiths, Frances; Lilford, Richard
Abstract : Introduction: Community health worker (CHW) programmes have low costs per person served and are central to achieving universal healthcare. However, their total cost is high and the target of one million CHWs for sub-Saharan Africa by 2015 was not met. We consider the affordability of rural CHW programmes by estimating total programme costs relative to national healthcare expenditure at different CHW salaries and resources available for healthcare. Methods: We combine an existing source of rural CHW programme costs with World Bank data to estimate relative CHW programme costs in 37 countries. We consider three 'salaries' (CHWs as volunteers, paid the local equivalent of US80 per month and paid the national minimum wage) and four potential healthcare budgets (both actual and Abuja declaration allocations alone and increased by external funding received and potential foreign aid, respectively). Costs are shown in 2012 nominal US. Results: With CHWs paid the local equivalent of US80 per month and financed from existing central government healthcare budgets, the median relative cost of a CHW programme would be 27% of the healthcare budget. While less than 2.5% in five countries (Botswana, Equatorial Guinea, Gabon, Namibia and South Africa), this relative cost would exceed 100% in three (Chad, Eritrea and Niger). There is a strong negative linear relationship (R 2 =0.83, p<0.001) between the natural logs of gross domestic product (GDP) per capita and affordability. In 23 countries with GDP per capita under US1200, the cost of a CHW programme would exceed 12% of actual healthcare spending if CHWs were paid US80 per month. Conclusion: CHWs may be a stepping stone to universal access to professional healthcare, but there is high variability in the affordability of CHW programmes across sub-Saharan Africa. In many countries, such programmes are not yet affordable unless significant foreign aid is received.